THE ROLE OF HUMAN CAPITAL IN VALUE CREATION: THEORETICAL INSIGHTS - Česynienė, Rima; Stankevičienė, Asta (Ekonomika, 2011)
The growth of the modern knowledge-based economy is becoming less dependent on tangible assets and, respectively, hinges more on the intangibles which are defined as human capital (HC). Despite the great number of scientific works dedicated to the HC phenomenon, the interest in this field had its “ups and downs” which caused changes not only in the notional concept itself, but also in the approach to its importance in value creation by measuring the returns of its investments. The purpose of the article is to analyse the evolution of these approaches. The nature of the article is both theoretical and analytical; it is based on quite an abundant list of scientific publications by Lithuanian and foreign authors. Adequate research methods were used in the study, such as a systematic analysis of scientific literature, logical comparative analysis and generalization. The originality of the study is ingrained in the fact that it reveals changes in the concept of human capital since its rise in the late 1960s until the most recent ideas which were formed and are still under development in the 2010s.